Debt, Investment, and Growth in Developing Countries with Segmented Labor Markets - Buffie, Edward (IMF Working Papers; Working Paper, 2020)
We introduce a new suite of macroeconomic models that extend and complement the Debt, Investment, and Growth (DIG) model widely used at the IMF since 2012. The new DIG-Labor models feature segmented labor markets, efficiency wages and open unemployment, and an informal non-agricultural sector. These features allow for a deeper examination of macroeconomic and fiscal policy programs and their impact on labor market outcomes, inequality, and poverty. The paper illustrates the model's properties by analyzing the growth, debt, and distributional consequences of big-push public investment programs with different mixes of investment in human capital and infrastructure. We show that investment in human capital is much more effective than investment in infrastructure in promoting long-run economic development when investments earn their average estimated returns. The decision about how much to invest in human capital versus infrastructure involves, however, an acute intertemporal trade-off. Because investment in education affects labor productivity with a long lag, it takes 15+ years before net national income, the private capital stock, real wages for the poor, and formal sector employment surpass their counterparts in a program that invests mainly in infrastructure. The ranking of alternative investment programs depends on the policymakers' social discount rate and on the weight of distributional objectives in the social welfare function.